2021
DOI: 10.1136/neurintsurg-2021-017865
|View full text |Cite
|
Sign up to set email alerts
|

Robotic-assisted intracranial aneurysm treatment: 1 year follow-up imaging and clinical outcomes

Abstract: BackgroundThe use of robotics in medicine may enable increased technical accuracy, reduced procedural time and radiation exposure, and remote completion of procedures. We have previously described the first-in-human, robotic-assisted cerebral aneurysm treatment using the CorPath GRX Robotic System. In this report we discuss our early experiences and outcomes using this robotic device for endovascular treatment of intracranial aneurysms using stent-assisted coil embolization and flow diversion.MethodsThe patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Through a manual reference search, we identified 1 work that met our inclusion criteria. Finally, we have included 7 works in this systematic review [ 8 14 ]. The full search strategy is depicted in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Through a manual reference search, we identified 1 work that met our inclusion criteria. Finally, we have included 7 works in this systematic review [ 8 14 ]. The full search strategy is depicted in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We have identified six original works focusing on the application of robotic devices for surgical interventions in aneurysm cases. Additionally, one work was identified as a follow-up to another study included in this review; we have included this work as part of the original investigation (Table 1 ) [ 8 ]. Four of these works originated from a US-Canadian collaboration, one was from the USA, one from France, and one from international collaboration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…7 One-year follow-up of this study showed four aneurysms that were completely obliterated and the remaining two occluded with a residual neck. 8 A subsequent study was performed on a cohort of 10 patients requiring carotid artery angioplasty and stenting, with 3 patients converted to manual catheterization mid-procedure due to encounter with unexpected bovine arch findings. 9 Also in 2020, Nogueira et al reported a single-center technical report of the first four consecutive cases of carotid artery stenting for the treatment of severe symptomatic carotid stenosis with ipsilateral strokes on presentation utilizing the CorPath GRX Robotic System (Corindus Inc., Waltham, MA).…”
Section: Robotic-assisted Neurointerventionsmentioning
confidence: 99%
“…This system has performed diagnostic cerebral angiography procedures and ten carotid artery stenting procedures (Nogueira et al, 2020;Sajja et al, 2020;Weinberg et al, 2021). Furthermore, it has been recently used to perform robotassisted, neuroendovascular interventions including aneurysm embolization and epistaxis embolization (Pereira et al, 2020;Cancelliere et al, 2022;Saber et al, 2022). These systems use a controller-operator structure, where operators remotely control and navigate a robot through a patient's vasculature to the target site.…”
Section: Introductionmentioning
confidence: 99%